2004
DOI: 10.1007/s11103-004-0641-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel alkaline α-galactosidase gene is involved in rice leaf senescence

Abstract: We previously isolated and identified numerous senescence-associated genes (SAGs) in rice leaves. Here we characterized the structure and function of an SAG- Osh69 encoding alkaline alpha-galactosidase that belongs to a novel family of glycosyl hydrolases. Osh69 is a single-copy gene composed of 13 exons located on rice chromosome 8. The expression level of Osh69 is not only up-regulated during natural leaf senescence but also induced rapidly by darkness, hormones (methyl jasmonic acid, salicylic acid), and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
74
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 66 publications
(60 reference statements)
0
74
0
4
Order By: Relevance
“…The expression of ZmAGA1 (Figure 2, number 5) in maize seedlings was enhanced by cold and drought, but not by sodium chloride (Zhao et al 2006). Rice Osh69 ( Figure 2, number 1) expression was up-regulated by dark and wounding (Lee et al 2004). The mode of stress responses in TtAGA1 was similar to the expression patterns of alkaline a-galactosidase genes in maize and rice, except that the TtAGA1 expression was enhanced by high salinity.…”
mentioning
confidence: 77%
“…The expression of ZmAGA1 (Figure 2, number 5) in maize seedlings was enhanced by cold and drought, but not by sodium chloride (Zhao et al 2006). Rice Osh69 ( Figure 2, number 1) expression was up-regulated by dark and wounding (Lee et al 2004). The mode of stress responses in TtAGA1 was similar to the expression patterns of alkaline a-galactosidase genes in maize and rice, except that the TtAGA1 expression was enhanced by high salinity.…”
mentioning
confidence: 77%
“…The results clearly indicated that the early senescence occurred in the OsDOS RNAi lines in an age-dependent manner. Moreover, two selected SAGs, Osh69 and Osl57 (Lee et al, 2001(Lee et al, , 2004, were expressed at higher levels in the RNAi leaves compared with the age-matched wild-type leaves, indicating that specific molecular events were in correlation with the overall physiology (Fig. 4, C and D).…”
Section: Rnai Knockdown Of Osdos Expression Caused An Accelerated Agementioning
confidence: 95%
“…Current understanding on leaf senescence in rice is limited to physiological and cytological studies, characterization of several senescence up-regulated genes (Inada et al, 1998(Inada et al, , 1999Lee et al, 2001Lee et al, , 2004Hung and Kao, 2004;Tang et al, 2005), rudimentary quantitative trait loci-based genetic analysis Abdelkhalik et al, 2005), and the isolation and characterization of a premature mutant (Li et al, 2005) and stay-green mutants (Cha et al, 2002). Importantly, previous studies revealed that 60% to 90% of total carbon in the panicles at harvest is derived from photosynthesis after heading (Mae, 1997), and that leaf senescence during reproductive and ripening stages is directly related to biomass production and grain yield of rice crop (Ray et al, 1983).…”
mentioning
confidence: 99%
“…The oligosaccharides are degraded during seed germination by the action of two distinct types of ␣-Gals that differ in their optimal pH of catalysis. While the acid ␣-Gal type is most likely active in the acidic environment of the vacuole and the apoplasm, the alkaline ␣-Gal type probably catalyzes galactose release in the more neutral or alkaline cytoplasm (4,17,31). Mammals express an ␣-Gal and an ␣-N-acetylgalactosaminidase (␣-NAGal) in lysosomal bodies to degrade glycolipids, glycoproteins, and oligosaccharides.…”
mentioning
confidence: 99%